Situation of small and middle sized enterprises in Northern Great Plain Region - Nagy, Csilla (Acta Agraria Debreceniensis, 2012)
Most of the enterprises operating in Hungary belong to the group of small and medium enterprises (SMEs) which means that their total number of staff is less than 250. The aim of the study is to examine SMEs operating within the North Great Plain region. It provides a short summary of the general characteristics of the region, the situation and significance of SMEs based on the data 2009 and it also clarifies the relevant definitions. The data shows that the enterprise type that is most characteristic in the the region is joint venture (the most popular type is Ltd). It can be laid down as a fact that the number of micro and sole entrepreneurs is also significant in the area. It is also clear that the majority of small enterprises deals with commerce, while most of the medium enterprises are involved in industry (processing industry). As a continuation of the examination, size of investments, influx of foreign capital, ratio of employed people and grant opportunities are also to be evaluated since these factors influence the operation of enterprises as well.